Monitoring tritrophic biocontrol interactions between Bacillus spp., Fusarium oxysporum f. sp. cubense, tropical race 4 and banana plants in vivo based on fluorescent transformation system - He, Ping; Li, Shu; Xu, Shengtao; Fan, Huacai; Wang, Yongfen; Zhou, Wei; Fu, Gang; Han, Guangyu; Wang, Yunyue; Zheng, Si-Jun (Frontiers Media, 2021)
Bacillus spp. are effective biocontrol agents for Fusarium wilt of banana, tropical race 4 (TR4). This study explores the colonization by B. subtilis, B. velezensis and B. amyloliquefaciens of host banana plants and elucidates the mechanism of antagonistic TR4 biocontrol. The authors selected one B. subtilis strain, three B. velezensis strains and three B. amyloliquefaciens strains that are proven to significantly inhibit TR4 in vitro, optimized the genetic transformation conditions and explored their colonization process in banana plants. The results showed that we successfully constructed an optimized fluorescent electro-transformation system (OD600 of bacteria concentration = 0.7, plasmid concentration = 50 ng/μL, plasmid volume = 2 μL, transformation voltage = 1.8kV, transformation capacitance = 400Ω) of TR4-inhibitory Bacillus spp. strains. The red fluorescent protein (RFP)-labelled strains were shown to have high stability with a plasmid-retention frequency above 98%, where bacterial growth rates and TR4 inhibition are unaffected by fluorescent plasmid insertion. In vivo colonizing observation by Laser Scanning Confocal Microscopy (LSCM) and Scanning Electron Microscopy (SEM) showed that Bacillus spp. can colonize the internal cells of banana plantlets roots. Further fluorescent observation by (LSCM) showed these RFP-labelled bacteria exhibit chemotaxis (chemotaxis ratio was 1.85±0.04) towards green fluorescent protein (GFP)-labelled TR4 hyphae in banana plants. We conclude that B. subtilis, B. velezensis and B. amyloliquefaciens can successfully colonize banana plants and interact with TR4. Monitoring its dynamic interaction with TR4 and its biocontrol mechanism is under further study.